Uncovering procedural knowledge in craft, design, and technology education: a case of hands-on activities in electronics - Matti Pirttimaa; Jukka Husu; Mika Metsärinne (Springer Netherlands, 2025)
Different knowledge types have their own specific features and tasks in the learning process. Procedural knowledge is used in craft and technology education when students solve problems individually and share their working knowledge with others. This study presents a detailed analysis of a one student’s learning process in technology education and the procedural knowledge used during learning tasks. Thus, procedural knowledge is mainly produced when acting, and includes students’ goal-directed actions related to the craft, design and technology processes and their learning content. These knowledge practices also include multiple interactions with teachers and other students. The findings show six different knowledge practices: observing, checking and asking, revising, guided representative action, self-directed representative action, and comprehended action. These knowledge practices actively relate to each other, and, in concert, they constitute chains of actions that constitute two different types of procedural knowledge: proactive knowledge and executive knowledge. We conclude by discussing how these knowledge practices can be used to develop our understanding of the teaching and learning of craft, design and technology.